Anatomical localization and clinical impact of sentinel lymph nodes based on patterns of pelvic lymphatic drainage in clinically localized prostate cancer. Issue 6 (25th January 2018) - Miki, Jun; Yanagisawa, Takafumi; Tsuzuki, Shunsuke; Mori, Keiichiro; Urabe, Fumihiko; Kayano, Sotaro; Yorozu, Takashi; Sato, Shun; Kimura, Takahiro; Takahashi, Hiroyuki; Kishimoto, Koichi; Egawa, Shin
Abstract : Background: Although sentinel lymph node in prostate has been generating renewed interest, its significance remains controversial due to inadequate evidence. Methods: We reviewed a prospective cohort of 50 consecutive patients with intermediate‐ to high‐risk localized prostate cancer who had undergone laparoscopic radical prostatectomy. Sentinel lymph node biopsy by fluorescence detection using intraoperative imaging with indocyanine green and backup extended pelvic lymph node dissection were conducted prior to prostatectomy. Intraoperative and pathological findings were elaborated and compared for confirmation. Results: Sentinel lymph nodes were successfully identified in 47 patients (94%). A median of four sentinel lymph nodes was detected per patient. Lymph node metastasis was confirmed in six patients (12%), all of whom had positive sentinel lymph nodes. Three typical pathways of lymphatic drainage related to sentinel lymph nodes from the prostate were recognized. Ninety‐one percent of the positive sentinel lymph nodes (10/11) were located at two predominant sites along these characteristic lymphatic pathways. One site was the junctional nodes, located at the junction between internal and external iliac vessels. The other was the distal internal iliac nodes, located along the inferior vesical artery. Conclusions: Over 90% of positive sentinel lymph nodes were identified at two predominant sites. Priority should be given to the removal of these sentinel lymph nodes, which are located closer to the prostate, in pelvic lymph node dissection. Particular attention should be paid to identifying these nodes to reduce the possibility of overlooking lymph node metastasis.